Class and Conflict: Social Divides in Vikram Seth’s A Suitable Boy - D.K. Kamble, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Vikram Seth’s A Suitable Boy (1993) presents a rich depiction of post-independence India, blending intimate family stories with the nation’s socio-political transformations in the early 1950s. This article examines how the novel portrays class struggles and societal rifts during a time shaped by partition recovery, India’s inaugural democratic elections, and land reform efforts. Through the interwoven narratives of families like the Mehras, Kapoors, Khans, and Chatterjis, Seth reveals economic disparities, caste prejudices, and religious tensions that fracture society. Key themes include the abolition of the zamindari system, highlighting divides between elites and labourers; interfaith relationships challenging communal norms; and familial dynamics mirroring broader cultural pressures. Employing a post-colonial lens, this study argues that Seth uses social realism to critique the enduring impact of colonial structures in a newly free nation, where progressive policies clash with entrenched traditions. By analyzing characters like Lata Mehra’s marital decisions and Mahesh Kapoor’s political efforts, the novel underscores the tension between individual choice and systemic barriers. Ultimately, A Suitable Boy acts as a microcosm of India’s nation-building challenges, emphasizing persistent conflicts that shape social cohesion in a diverse society. This analysis contributes to understanding how literature reflects class-based divisions in transformative periods.
Keywords: Vikram Seth; A Suitable Boy; class conflict; social divides; post-independence India; zamindari abolition